Murder gets a makeover ebook - Levine, Laura (Jaine Austen Mystery, 2021)
The latest in acclaimed TV comedy writer and novelist Laura Levine's witty, lighthearted mystery series featuring Hollywood-based freelance writer Jaine Austen and her snarky cat, Prozac—a laugh-out-loud read for fans of Joanne Fluke, Miranda James, and Laura Childs. Uber-stylist Bebe Braddock plans to juice up her Instagram feed and thinks Jaine would make a perfect "Before & After" model. At Lance's insistence Jaine is ushered into Bebe's sprawling Brentwood spread to await her transformation. Yet, while the surroundings are glamorous, the atmosphere is toxic as Bebe bullies her team of assistants, and even her husband, into obeying her every whim. Having earned the wrath of everyone in her orbit, few are shocked when Bebe is found strangled with one of her detested wire hangers. But Jaine's prints are all over the murder weapon, making her a prime suspect. The police, however, aren't the only ones showing interest in her—so is Justin, Bebe's very cute, very young personal assistant. While Jaine navigates a cougar-style romance, Prozac is mistakenly hailed as a feline hero and catapults into internet fame. Still, there are more urgent matters at hand than Prozac's swelling ego. Unless Jaine can track down Bebe's killer and clear her own name, the only new outfit she'll be modeling is an orange prison jumpsuit . . . "As always, Levine's spunky heroine gets the last laugh." —Kirkus Reviews "For lovers of the zany this is a sure thing." —Booklist